Evaluation of protein sparing effect in Nile tilapia Oreochromis niloticus fed with organic selenium supplemented diet - Pattipeilohy, Christian Ernsz; Suprayudi, Muhammad Agus; Setiawati, Mia; Ekasari, Julie (Jurnal Akuakultur Indonesia, 2020)
ABSTRACT The objective of this research was to determine the optimum level of organic selenium supplementation in improving the growth performance of Nile tilapia Oreochromis niloticus fed with diet containing low protein level. Basal diet was formulated to contain 28% protein with three different levels of organic selenium supplementation, namely 0 (control), 3, and 6 mg Se/kg feed. Furthermore, to evaluate selenium function on protein utilization and sparring effect, a diet with 30% of protein content was also used as a comparison. In this regard, this study was conducted using a completely randomized experimental design with four treatments and three replications. Nile tilapia with an average body weight of 8.05 ± 0.25 g were reared in the 100×50×50 cm3 aquarium at a density of 15 fish/aquarium. The experimental fish were reared for 60 days and fed three times daily to apparent satiation levels. Dietary supplementation of organic Se resulted in higher fish biomass, lower feed conversion ratio, higher protein retention and daily growth rate compared to the control diets with 28% and 30% protein levels. In conclusion, dietary supplementation of organic Se at 3 mg organic Se/kg feed could significantly increase protein utilization and improve the growth performance of Nile tilapia. Keywords: tilapia, protein sparing effect, organic selenium, feed ABSTRAK Tujuan dari penelitian ini adalah menentukan tingkat suplementasi selenium organic pada pakan untuk meningkatkan kinerja pertumbuhan ikan nila Oreochromis niloticus. Pakan basal diformulasikan mengandung 28% protein dengan tiga tingkat selenium organik yaitu 0 (kontrol), 3, dan 6 mg Se/kg pakan. Selanjutnya untuk mengevaluasi penggunaan selenium pada pemanfaatan protein dan efek sparring, pakan dengan 30% protein juga ditambahkan sebagai perlakuan pembanding. Penelitian ini menggunakan rancangan acak lengkap dengan empat perlakuan dan tiga ulangan. Ikan nila dengan bobot rata-rata adalah 8.05 ± 0.25 g dipelihara dalam akuarium 100 × 50 × 50 cm3 dengan kepadatan 15 ikan/akuarium. Ikan dipelihara selama 60 hari dan diberi pakan tiga kali sehari secara at satiation. Pemberian pakan dengan suplementasi Se organic menghasilkan biomassa ikan yang lebih tinggi, rasio konversi pakan yang lebih rendah, retensi protein dan laju pertumbuhan harian yang lebih tinggi daripada perlakuan control dengan kadar protein 28% dan 30%. Berdasarkan hasil penelitian ini, dapat disimpulkan bahwa suplemtasi pakan ikan nila dengan 3 mg Se organik/kg pakan dapat meningkatkan pemanfaatan protein pakan dan kinerja pertumbuhan ikan Nila. Kata kunci: ikan nila, protein sparing effect, selenium organik, pakan.